Realitization and Testing of Mini Extruder for Biomaterial Filament in Biomedical Application - Yudan Whulanza (University of Muhammadiyah Malang, 2016)
The use of biomaterials in tissue engineering technique requires an engineered scaffold that allow the cells to be growth. Therefore, a specific biomaterial is required to provide a supportive environment for the seeding cell. This study focused on the design and realization of mini-extruder to produce a biocompatible filament material. Later, the filament is applied in a fused deposition modelling to realize biocompatible scaffold. The extruder uses a single screw extruder of 25mm diameter with compression ratio of 2. Moreover, the extruder has an effective length of 305mm with a screw length ratio of the feed zone and metering zone by 20% and 40%. A forming die used has a diameter of 1.7mm. At the end of the realization step, the device was tested to produce the filament with various parameters which are screw rotational speed, winding speed, temperature and torque. Characterization of the produced filaments were done by measuring the diameter of filaments using the material of polycaprolactone (PCL). The filament results have a range of 0.05-1.48mm in diameter during the testing process.